A Concrete Situation For Learning Decimals - Pramudiani, Puri; Zulkardi, Zulkardi; Hartono, Yusuf; Amerom, Barbara van (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2011)
Learning about decimals is an important part in mathematics. HoweverÃ‚Â at the same time, decimals are known as the Ã‚Â abstract numbers forÃ‚Â students. Mostly in Indonesia, decimal is taught only as anotherÃ‚Â notation for fractions or percentages. There are no meaningfulÃ‚Â references Ã‚Â for Ã‚Â them Ã‚Â such as Ã‚Â the Ã‚Â use of Ã‚Â concrete Ã‚Â situations. This studyÃ‚Â aimed at investigating one situation that enables students to learn aboutÃ‚Â decimals in a meaningful way, Ã‚Â i.e. Ã‚Â measurement Ã‚Â activities. Ã‚Â DesignÃ‚Â research was chosen to reach the research goal. Realistic MathematicsÃ‚Â Education (RME) underlies Ã‚Â the design Ã‚Â of Ã‚Â context and activities. OurÃ‚Â findings are that the students could discover decimals and Ã‚Â getÃ‚Â meaningful situation from it. Measurement activities can promote theÃ‚Â studentsÃ¢â‚¬â„¢ notion of decimals which, then, provoke the studentsÃ¢â‚¬â„¢Ã‚Â thinking into the idea of using number line as a model for placing theÃ‚Â magnitude of decimals. Based on these findings, it is recommended thatÃ‚Â RME be implemented as an approach of teaching and learningÃ‚Â decimals.Keywords: decimals, Realistic Mathematics Education (RME), numberÃ‚Â line, design research.Ã‚Â DOI: http://dx.doi.org/10.22342/jme.2.2.750.215-230